Navigating the Quarter-Life Crisis: Exploring Suffering Self-Transcendence among UIN Sunan Ampel Surabaya Students - Permata, Reynata Ayu; Abdul Fattah (Faculty of Ushuluddin and Philosophy, 2023)
The Quarter Life Crisis phenomenon generally occurs between the ages of 20 and 30, when individuals feel depressed and anxious about their future, including their career, social relationships, and personal life. During this phase, individuals often feel that their lives are controlled by fate and cannot be changed. The concept of suffering in this study is seen as a physical and psychological experience involving mental reactions to external conditions. This study aims to understand the essence of suffering and the process of self-transcendence among UIN Sunan Ampel Surabaya students experiencing the Quarter Life Crisis phase. Using a descriptive qualitative approach, data were collected through in-depth interviews and observations of respondents who met the criteria of age, experience of suffering, and involvement in social organizations. Wong’s Self-Transcendence Theory analyzes how individuals can overcome suffering by focusing on positive aspects of their lives and finding meaning through self-reflection and meaningful activities. The results of this study indicate that suffering experienced during the Quarter Life Crisis can serve as a means for self-reflection and improving the quality of life, as well as helping individuals achieve a higher level of understanding of their life goals and spiritual relationships.